2019
DOI: 10.2298/psi181229014i
|View full text |Cite
|
Sign up to set email alerts
|

Does handedness matter? Writing and tracing kinematic analysis in healthy adults

Abstract: Writing is a complex skill and it can be affected by many factors. One of the most obvious is handedness. The actual influence of handedness (especially left-handedness, since almost 10% of the population is left-handed) onto writing performance has not been fully studied in previous research. Digitalized kinematic analyses and assessments of writing strategies (i.e., graphic rules and principles) are two approaches to investigating writing characteristics poorly addressed in previous research. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Finally, our research lacks a right-handed control group, which would have allowed a direct comparison of converted left-handers' right-hand writing performance with that of innate right-handers. However, previous studies found few 59,60 to no differences 7 between right-and left-handers' handwriting kinematics despite slight differences in biomechanics.…”
Section: Strengths and Limitationsmentioning
confidence: 87%
“…Finally, our research lacks a right-handed control group, which would have allowed a direct comparison of converted left-handers' right-hand writing performance with that of innate right-handers. However, previous studies found few 59,60 to no differences 7 between right-and left-handers' handwriting kinematics despite slight differences in biomechanics.…”
Section: Strengths and Limitationsmentioning
confidence: 87%
“…Previous studies demonstrated that attention facilitated behavioral performance in individual sensory modalities. Furthermore, attentional increases were noted in the amplitude of early and middle latency components of event-related brain potentials (ERPs) elicited by somatosensory stimulation (Desmedt and Robertson, 1977;Garcia-Larrea et al, 1995;Eimer et al, 2002;van Velzen et al, 2002;Valeriani et al, 2003;Kida et al, 2004b,c;Forster and Eimer, 2005;Kida et al, 2006;Gherri and Eimer, 2008;Press et al, 2008;Adler et al, 2009;Keil et al, 2017;Novicic and Savic, 2023;Savic et al, 2023). Auditory spatial selective attention exerts two types of effects on N1 amplitude: the superimposition of another negativity (processing negativity, PN, or its negative difference between attended and unattended channels, Nd) and the enhancement of N1 itself (Hillyard et al, 1973;Naatanen et al, 1978;Naatanen, 2000), and visual spatial attention also exerts both of these effects on amplitudes in the N1-P2 latency range (Johannes et al, 1995;Hillyard and Anllo-Vento, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Specific kinematic parameters of writing can be derived from strokes and these are: on surface pressure, stroke speed, stroke duration, velocity, acceleration, jerk, number of velocity/acceleration direction alteration, hand in-air/on-surface time, horizontal/vertical/tangential velocity (acceleration/jerk) and others [6][7][8][9][10]. Various psychiatric and neurological disorders often have their own unique combination of kinematic parameters in particular writing task in which they deviate from healthy controls [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%